Towards a competitive European Internet industry A socio-economic analysis of the European Internet industry and the Future Internet Public-Private Partnership - Hoorens, Stijn (RAND Corporation, 2012)
This report analyses challenges and opportunities for the EU Internet industry and estimates the impact of investing in a Future Internet PPP. It finds that there is enormous economic potential for Europe, but only if some tough choices are made.